2017
DOI: 10.1002/ldr.2663
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biology Changes as a Consequence of Organic Amendments Subjected to a Severe Drought

Abstract: Effect of severe drought events in combination with organic amendments (municipal solid waste, MSW, sheep manure, SM, and cow manure, CM) on soil dehydrogenase, urease, β‐glucosidase and phosphatase activities and microbial community by analyzing phospholipid fatty acids was studied under controlled laboratory conditions for one year. Two levels of irrigation were used: (1) watered soils, where the soils were maintained at 60% of their water holding capacity through the experiment, and (2) non‐watered soils, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 81 publications
3
8
0
Order By: Relevance
“…Subsequently, a larger microbial biomass might have formed and their activity catalysed decomposition of residues and corresponding release of essential nutrients for further microbial growth and activity (Srinivasarao et al 2018;Roy et al 2019;Rawat et al 2019). Our findings of higher DHA were in agreement with the research outcomes reported by Franco-Andreu et al (2017) and the impact of soil moisture stress was more prominent on the DHA than the SMBC (Table 2)…”
Section: Soil Microenvironmentsupporting
confidence: 89%
“…Subsequently, a larger microbial biomass might have formed and their activity catalysed decomposition of residues and corresponding release of essential nutrients for further microbial growth and activity (Srinivasarao et al 2018;Roy et al 2019;Rawat et al 2019). Our findings of higher DHA were in agreement with the research outcomes reported by Franco-Andreu et al (2017) and the impact of soil moisture stress was more prominent on the DHA than the SMBC (Table 2)…”
Section: Soil Microenvironmentsupporting
confidence: 89%
“…This is consistent with previous findings (Marschner, Kandeler, & Marschner, ; Melero, Porras, Herencia, & Madejon, ; Song et al, ). The increase in water holding capacity we observed (Table ) is typical of additions of organic fertilizer, especially in degraded soils (Franco‐Andreu et al, ; Mabuhay, Nakagoshi, & Isagi, ), where improvements in plant available water have significantly positive effects on crop yield (Lal, ). In the present study, organic inputs supported growth of Fusarium and Chaetomiaceae , which were both identified as keystone taxa, playing central roles in the decomposition of residues (Banerjee et al, ).…”
Section: Discussionmentioning
confidence: 63%
“…1 and 2). A different composition of the microbial structure could be expected due to the different irrigation regime and organic amendment management, as reported by Franco-Andreu et al (2016a, 2016b and Sun et al (2017). These authors reported that non-irrigated soils have been related to a higher proportion of Gram-positive bacteria than in irrigated soils because of the higher rigidity of cell walls compared to Gram-negative bacteria.…”
Section: Effect Of Herbicides Residues Organic Amendments and Irrigamentioning
confidence: 80%